Vertical evaluation of air quality improvement by urban forest using unmanned aerial vehicles - Miao, Chunping; Cui, Aiwei; Xiong, Zaiping; Hu, Yuanman; Chen, Wei; He, Xingyuan (Frontiers in Ecology and Evolution, 2022)
Urban forest is considered as an effective strategy for mitigating urban air pollution via deposition, absorption and dispersion processes. However, previous researches focused mainly on the deposition effect or removal capacity near ground, while, the net effect of urban forest on air quality is rarely evaluated in the vertical dimension. In this study, PM2.5, PM10, CO, SO2, NO2 and O3 concentrations, air temperature, relative humidity and atmosphere pressure at 0, 2.5 m, 5 m, 10 m, 15 m, 20 m, 30 m, 40 m, 60 m, 80 m and 100 m in urban forest, street and community areas were collected by unmanned aerial vehicles equipped with Sniffer4D V2 on overcast and sunny days. The PM, CO, NO2, and O3 concentrations increased with height below 20 m and then slightly decreased with height on the overcast day, whereas SO2 concentrations decreased with height within 20 m. The urban forest increased PM concentrations in the morning of the overcast day, whereas decreased PM concentrations in the afternoon on the overcast day. The forest obstructed PM dispersion from the canopy when PM concentrations grew lower in the morning, but it hindered PM from deposition when PM concentrations grew higher in the afternoon.